At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Ask your questions and receive precise answers from experienced professionals across different disciplines. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

How do you solve the answer to this
-6(-3)(-2)


Sagot :


First of all, a negative times a negative times a negative would end up as a negative, so we got that covered. Now all we need is the arithmetic part. 6 x 3 = 18, and 18 x 2 = 36 

So you're final answer would be -36 

so if 2 number with the same sign are multiplied togher, the result will be positive
so if (-) times (-)=(+)
and (+) times (-)=(-)
then
(-) times (-) times (-)=(-)

so just multiply them so
-6 times -2=+12
+12 times -3=-36